SPATIAL DISTRIBUTION OF SEA SURFACE TEMPERATURE IN WEST SUMATERA SEAWATERS ASSOCIATED WITH INDIAN OCEAN DIPOLE (IOD) EVENT IN TRANSITIONAL SEASONS (AUGUST-OCTOBER) (Case Study: Pasumpahan and Sibonta Island) - Wisha, Ulung Jantama; Tanto, Try Al; Ilham, Ilham (Badan Informasi Geospasial in Partnership with MAPIN, 2016)
Along with the issue of climate change which is characterized by an increase in global temperature, the sea surface temperatures (SST) also allegedly helped change that has direct and consequential to the phenomenon of coral bleaching that occurred in the waters Pasumpahan, Sibonta and several other areas in West Sumatra. The purpose of this study was to identify anomalies in the sea surface temperature in the waters Pasumpahan and Sibonta due to the influence of the phenomenon of Indian Ocean Dipole. The method used is purposive quantitative with perform spatial analysis (Inverse Distance Weighted). Primary data are consisted of SST and tide data which measured using the HOBO U20 titanium water level data logger. The secondary data are consisted of RBI map, Google eye image and tide forecast. SST around Pasumpahan waters ranged from 30-30,6oC and Sibonta waters ranged from 30,1-30,6°C. At a depth of 25 meters, Pasumpahan waters temperature ranged from 29,152-30,457°C and Sibonta waters temperature ranged from 26,28-28,5°C, the surface elevation ranged from 0,83 to 1,17 m from MSL point, rainfall average in August until October ranged from 5,64-7,71 mm. The rainfall, temperature and surface elevation changes are affecting each other. Temperature anomalies occurred in the Sibonta waters due to the closer location with Indian Ocean, directly influence to Sibonta waters temperature that is relatively volatile.